2022
DOI: 10.1155/2022/7179733
|View full text |Cite|
|
Sign up to set email alerts
|

miR-887-3p Inhibits the Progression of Colorectal Cancer via Downregulating DNMT1 Expression and Regulating P53 Expression

Abstract: Colorectal cancer (CRC) is the third most diagnosed cancer worldwide and the second leading cause of cancer-related deaths. Many researchers have reported that abnormal microRNAs (miRs) were expressed in CRC and participated in the occurrence and progression of CRC. However, there are few reports of miR-887-3p regulating CRC development. In the current study, we investigated the abnormal expression of miR-887-3p and also demonstrated its regulatory role and detailed molecular mechanism in CRC. Initially, miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Colorectal cancer (CRC) is a common cancer that is estimated to have more than 1 million new cases a year globally ( 1 ). Most CRC cases are sporadic with no family history or significant genetic predisposition, and people >50 years are at the highest risk ( 2 ). A study has shown that the cumulative incidence of liver metastasis in patients with CRC in 5 years is up to 15% ( 3 ), and another study has shown that the incidence of liver metastasis within 5 years after diagnosis of CRC is up to 26.5% ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is a common cancer that is estimated to have more than 1 million new cases a year globally ( 1 ). Most CRC cases are sporadic with no family history or significant genetic predisposition, and people >50 years are at the highest risk ( 2 ). A study has shown that the cumulative incidence of liver metastasis in patients with CRC in 5 years is up to 15% ( 3 ), and another study has shown that the incidence of liver metastasis within 5 years after diagnosis of CRC is up to 26.5% ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, scholars have devoted themselves to studying the relevant factors of the occurrence and development of various malignant tumors (36)(37)(38)(39)(40). This can provide a theoretical basis for the prevention and treatment of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A cerebral hemorrhage in the basal ganglia is the most common type of hypertensive cerebral hemorrhage (13). Imaging and other indicators have important diagnostic and therapeutic significance in a variety of diseases (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%